2014
DOI: 10.1159/000343854
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials of Combined Molecular Targeted Therapy and Locoregional Therapy in Hepatocellular Carcinoma: Past, Present, and Future

Abstract: Background: Sorafenib, a multikinase inhibitor that targets angiogenesis in hepatocellular carcinoma (HCC), has become a standard treatment for advanced-stage HCC and has shown survival benefits in recent clinical trials. Transarterial chemoembolization (TACE) and sorafenib are currently standard treatments for intermediate and advanced-stage HCC, respectively. Combined locoregional therapy, including TACE and molecular targeted therapies such as sorafenib, is an issue under active investigation in an attempt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 46 publications
(5 reference statements)
0
44
0
Order By: Relevance
“…Overall survival times were 8.4 and 8.2 mo for sorafenib and other treatments, respectively, and the difference was not significant [82,83] . To improve the efficacy of sorafenib, combination therapy or a multidisciplinary approach may be needed [84] . Several newer molecular target therapeutic agents were evaluated in clinical trials.…”
Section: Molecular Target Therapiesmentioning
confidence: 99%
“…Overall survival times were 8.4 and 8.2 mo for sorafenib and other treatments, respectively, and the difference was not significant [82,83] . To improve the efficacy of sorafenib, combination therapy or a multidisciplinary approach may be needed [84] . Several newer molecular target therapeutic agents were evaluated in clinical trials.…”
Section: Molecular Target Therapiesmentioning
confidence: 99%
“…Other studies have already shown a similar increase in the survival rate of patients treated with sorafenib after TACE, hypothesizing that the prolonged survival would be achieved in these patients because sorafenib can control VEGF levels, which increase after TACE [12].…”
Section: Discussionmentioning
confidence: 76%
“…One of the first randomized studies showed a longer time for the disease progression in patients with intermediate tumor stage [9]. Many other studies have been conducted worldwide, but when they are critically analyzed the authors have no doubts that more studies are needed to provide more reliable data about the indications of treatment combining TACE and sorafenib [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a natural polysaccharide composed of randomly distributed β- [1][2][3][4]-linked D-glucosamine and N-acetyl-D-glucosamine. Low molecular weight chitosan (LMWC) can be used as a carrier for RNAi drugs directed against VEGF (106).…”
Section: Polysaccharides Targeting Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…HCC represents the most common histological type of liver cancer, accounting for 70-85% of cases (2). Its treatment may include local ablation, surgical resection, trans-catheter arterial chemoembolization and the administration of chemotherapeutic agents (3,4). However, at the time of their diagnosis, HCC tumors may be too large or may have expanded into nearby major blood vessels or metastasized, rendering the majority of HCC patients unsuitable for treatment by surgical resection (5).…”
Section: Introductionmentioning
confidence: 99%